Effects of Migration Elsewhere and Zimbabwe - Winniefridah Matsa (Springer, Cham, 2023)
Effects of migration cannot be generalised for all countries. Migration may have both positive and negative effects on both the source and destination countries. The positive benefits include remittances which increase the standard of living and improve household budgets enabling migrants’ children to increase enrolments in schools, thereby increasing also retention and advancement. The negative have to do with educational outcomes (performances) because of the level of educational support from illiterate caregivers. Migration reduces aspirations to higher education emanating from the influence of a culture of migration fostered among children despite increased remittances for schooling. This chapter focuses on benefits of parental migration, the attitude of learners and parents towards migration and schooling as well as effects of migration on children’s aspirations and performance.